2016
DOI: 10.3390/ijms17101615
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Patterns of Brain Metastases in Breast Cancer Patients: A Subproject of the German Brain Metastases in Breast Cancer (BMBC) Registry

Abstract: Evidence about distribution patterns of brain metastases with regard to breast cancer subtypes and its influence on the prognosis of patients is insufficient. Clinical data, cranial computed tomography (CT) and magnetic resonance imaging (MRI) scans of 300 breast cancer patients with brain metastases (BMs) were collected retrospectively in four centers participating in the Brain Metastases in Breast Cancer Registry (BMBC) in Germany. Patients with positive estrogen (ER), progesterone (PR), or human epidermal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
18
0
2
Order By: Relevance
“…In a small cohort, HR-negative/HER2-positive breast cancer patients with BMs were more likely to present with occipital metastases [11]. Laakmann et al have published results on brain imaging of 400 breast cancer patients with BMs, of whom 102 had HER2-positive primary tumours, and observed also a correlation between HER2 positivity and metastases in the posterior fossa [12]. Here, we could confirm this finding in 314 patients with HER2-positive breast cancer in the BMBC registry.…”
Section: Discussionmentioning
confidence: 99%
“…In a small cohort, HR-negative/HER2-positive breast cancer patients with BMs were more likely to present with occipital metastases [11]. Laakmann et al have published results on brain imaging of 400 breast cancer patients with BMs, of whom 102 had HER2-positive primary tumours, and observed also a correlation between HER2 positivity and metastases in the posterior fossa [12]. Here, we could confirm this finding in 314 patients with HER2-positive breast cancer in the BMBC registry.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the metastasis in the brain has been shown to be associated with prognosis. Through MRI, a poor prognosis for patients with leptomeningeal disease was shown in several studies, 8,10 in comparison to nonleptomeningeal. 10 In one of these studies with a relatively high number (300) of BCBM patients a shorter survival was also observed in patients with metastases in the occipital lobe compared to other brain regions.…”
Section: Mri In the Prediction Of Prognosis Of Bcbmmentioning
confidence: 99%
“…Several risk factors for the development of seizures in patients with BM are described in the literature: For example, patients with a single BM, detection of tumoral hemorrhage, or supratentorial BM are at a higher risk [ 24 ]. Our previous analysis of the BMBC Registry showed that patients with positive estrogen or progesterone status have a lower number of BMs at diagnosis [ 25 ]. Thus, possibly a lower number of BMs in luminal-like patients could explain the higher probability of seizures.…”
Section: Discussionmentioning
confidence: 99%